2008
DOI: 10.1080/09603120701842864
|View full text |Cite
|
Sign up to set email alerts
|

Housing characteristics, home environmental factors and respiratory health in 3945 pre-school children in China

Abstract: The objective of the study was to assess the effects of housing characteristics and home environmental factors on respiratory symptoms of Chinese children. A cross-sectional study of 3945 children aged 1-6-years-old was conducted at 24 randomly selected kindergartens in Liaoning province, northeast China during April 2007. Information on respiratory symptoms (persistent cough, persistent phlegm, doctor-diagnosed asthma, current asthma, current wheeze and allergic rhinitis) and exposures to home environmental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
1
17
0
2
Order By: Relevance
“…This finding was consistent with the cross-sectional study of 14077 Swedish children aged 1-6 years, which reported four "dampness" indices including visible molds and windowpane condensation were associated with children's asthma, rhinitis and eczema symptoms [21]. In China, Dong et al [22][23][24] reported that signs in the home of water damage or visible mold on walls were positively associated with children's asthma symptoms in preschool children and elementary children in northeastern area of China. A recently published 10-year longitudinal study of adults in Uppsala, Sweden, found that signs of dampness in floor construction of any workplace building during follow up (cumulative exposure) were associated with incidence of mucosal symptoms (OR=2.43) including nasal catarrh, nasal obstruction, dryness in throat, sore throat or irritating cough [25].…”
Section: Discussionsupporting
confidence: 79%
“…This finding was consistent with the cross-sectional study of 14077 Swedish children aged 1-6 years, which reported four "dampness" indices including visible molds and windowpane condensation were associated with children's asthma, rhinitis and eczema symptoms [21]. In China, Dong et al [22][23][24] reported that signs in the home of water damage or visible mold on walls were positively associated with children's asthma symptoms in preschool children and elementary children in northeastern area of China. A recently published 10-year longitudinal study of adults in Uppsala, Sweden, found that signs of dampness in floor construction of any workplace building during follow up (cumulative exposure) were associated with incidence of mucosal symptoms (OR=2.43) including nasal catarrh, nasal obstruction, dryness in throat, sore throat or irritating cough [25].…”
Section: Discussionsupporting
confidence: 79%
“…Two Asian studies from Singapore also reported higher risks for rhinitis and rhinoconjunctivitis among 1-12-yr-old children [25,65]. The remaining six studies did not observe any statistically significant exposure-response relationships [17,22,26,44,47].…”
Section: Allergic Rhinitismentioning
confidence: 98%
“…DIJKSTRA [29] DALES [16] DALES [32] PONSONBY [18] ZHENG [27] CHEN [25] FREEMAN [20] FREEMAN substudy [20] SPENGLER [19] PEKKANEN [33] DONG [17] DONG [22] ANTOVA [15] WARMAN [24] Summary (OR FAGBULE [34] VERHOEFF [31] LI [26] LI [35] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] BRUNEKREEF [21] STRACHAN [37] STRACHAN [38] DIJKSTRA [29] DALES [16] SPENGLER [19] EMENIUS [36] ALPER [39] DONG [17] DONG [22] ANTOVA [15] ROSENBAUM [43] IOSSIFOVA [8] KARVONEN [42] Summary (OR LI [26] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] CHEN [25] BIAGINI [45] IBARGOYEN-ROTETA [44] KOSKINEN substudy [47] KOSKINEN [47] LI [26] LI [35] BRUNEKREEF [21] DONG …”
Section: Discussionmentioning
confidence: 99%
“…National surveys of asthma in Chinese children aged 0-14 years in 1990 and 2000 by the Childhood Asthma Collaborative Group of China [41] as well as a number of other studies indicate that asthma and allergies have increased in China [4,7,[42][43][44][45][46][47][48][49][50][51]. However, information about indoor exposure has been included to only a small extent and in only a few studies [52,53].…”
mentioning
confidence: 99%